Management of Sustainable Marine Tourism Through Scuba Diving in Gili Lampu Sambelia East Lombok - ., Syukriati; Zulfa, Aulia Diana; ., Jumaidin; Johari, Muhamad (Akademi Komunitas MAPINDO, 2024)
Indonesia is an archipelagic country which has a wider water area of 7,81 million km2 than its land area of 2.01 million km2 and is known as a maritime country. Due to the vast territorial waters of Indonesia, Indonesia is rich in its beautiful marine natural resources with a wide variety of marine life living in it. One of the water areas that is rich in the diversity of marine life is the marine tourism object Gili Lampu, which is located in Sambelia District, East Lombok. To manage its natural resources well, it is necessary to have the right concept to develop marine tourism in Indonesia, sustainable tourism is one of the best indicators in developing tourism based on natural resources by paying attention to environmental conservation. To realize the concept of development and management in the Gili Lampu marine tourism object, several efforts are needed to achieve it. The purpose of this study was to determine the management of sustainable marine tourism through scuba diving sports tourism in Gili Lampu, Sambelia,east Lombok The approach used in this research is qualitative method with descriptive research type. The results of the study stated that scuba diving tourism was able to become a means of marine conservation in realizing tourism development in Gili Lampu tourism objects. However, several obstacles were found in the process of developing and managing the Gili Lampu marine tourism object such as the low human resources in the field of tour guides, and the lack of a role in promoting scuba diving tourism by the manager of the Gili Lampu marine tourism object. Keywords: Development, Management, Human Resource, Tourist Guide, Scuba Diving